The centrality of aiua (blood) in the theology of the Epistle to the Hebrews an exegetical and philological study - Kuma, Hermann V. A. (Lewiston, N.Y. : Edwin Mellen Press, 2012)
This book demonstrates that because blood sanctifies, consecrates and purifies, the Greek word for blood provided the best expression for the unique role of Christ as self-sacrificing High Priest in the Epistle to the Hebrews.
Chapter One. Introduction -- Chapter Two. Review of literature -- Chapter Three. Old Testament background of aiua -- Chapter Four. Aiua in the New Testament world -- Chapter Five. Aiua in the Epistle to the Hebrews -- Chapter Six. Conclusions and implications -- Bibliography -- Author's index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Theology; Blood in the Bible; Bible. N.T. Hebrews -- Criticism, interpretation, etc; Gospel of truth -- Criticism, interpretation, etc; Preaching -- History -- Early church, ca. 30-600.; Rest -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Rest -- Religious aspects -- Gnosticism -- History of doctrines; Rest in the Bible; Religion; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Electronic books